Inquiry, engagement, and literacy in science: a retrospective, cross-national analysis of PISA 2006 - McConney, Andrew; Oliver, Mary C.; Woods-McConney, Amanda; Schibeci, Renato; Maor, Dorit (Wiley, 2014)
In this study, we examine patterns of students’ literacy and engagement in science associated with different levels of ‘inquiry-oriented’ learning reported by students in Australia, Canada, and New Zealand. To achieve this we analysed data from the Organisation for Economic Co-operation and Development’s (OECD) 2006 Programme for International Student Assessment (PISA) which had science as its focus. Consistently, our findings show that science students who report experiencing low levels of inquiry-oriented learning activities are found to have above average levels of science literacy, but below average levels of interest in science, and below average levels on six variables that reflect students’ engagement in science. Our findings show that the corollary is also true. Across the three countries, students who report high levels of inquiry-oriented learning activities in science are observed to have below average levels of science literacy, but above average levels of interest in learning science, and above average engagement in science. These findings appear to run counter to science education orthodoxy that the more students experience inquiry-oriented teaching and learning, the more likely they are to have stronger science literacy, as well as more positive affect towards science. We discuss the implications of these findings for science educators and researchers.